Development of Walking Analysis Learning Media Based on an E-Book Guide - Irawan, Fajar Awang; Junaidi, Said; Permana, Dhias Fajar Widya; Setyowati, Anies; Ghassani, Dina Syarafina; Prastiwi, Tania Arlita Safitri; Trans, MInh Nghia Le (Universitas Negeri Semarang, 2023)
The development research carried out aims to produce a product in the form of an e-book guide that is useful as a medium for walking analysis and preventing injuries during sports. This study uses a research method called Research and Development (R & D). The total sample size in the small trial was 10, and the full sample size in the field trial was 100. The sample has agreed to data collection by filling out informed consent and is willing to participate in the study from start to finish. Based on the results of this study, the e-book guide media feasibility validation results obtained a percentage of 93.75% for material and 87.5% for media. The results of the level of acceptance of this product by Sports Science students at Semarang State University showed a figure of 51.85% of the total sample being satisfied with the product. This e-book guide contains several materials, including basic movements; locomotor motion; non-locomotor motion; walking motion; gait analysis; injuries and handling; and the last material is suggestions and recommendations. For further research, we can discuss the effectiveness of flipbook-based learning media on the level of student knowledge.